PENGARUH UKURAN PERUSAHAAN DAN UKURAN KANTOR AKUNTAN PUBLIK TERHADAP AUDIT DELAY PADA PERUSAHAAN MANUFAKTUR SUBSEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BEI TAHUN 2017-2019 - Nilam Sari Simbolon; Harlyn Siagian (Jurnal Ekonomis, 2021)
The purpose of this study is to examine how much significant the influence between the size of company and the size of public accounting firm to audit delay partially or simultaneously. Approach this study uses quantitative methods. Determination of the sample by applying purposive sampling method, so that the obtained 54 samples sourced from the 18 food and beverage companies listed in Indonesia Stock Exchange since 2017-2019. Independent variables in this research is the size of the company and the size of public accounting firm, while the dependent variable is the audit delay. The technique of data analysis with the classical assumption test, descriptive statistics, and multiple linear regression. Through the entire test analysis of the obtained results that: (1) the size of company does not have a significant effect partially on audit delay, evidenced by the significance value of the T test at 0,565. (2) the size of public accounting firm has a negative effect on audit delay, evidenced by the significance value of the T test at -2,717 (3) the size of company and the size of public accounting firm have a significant effect simultaneously on the audit delay, which is evidenced by the significance value at 0,01.